The influence of changes in trunk and pelvic posture during single leg standing on hip and thigh muscle activation in a pain free population - Prior, S.; Mitchell, T.; Whiteley, R.; O'Sullivan, Peter; Williams, B.; Racinais, S.; Farooq, A. (BioMed Central Ltd., 2014)
Background: Thigh muscle injuries commonly occur during single leg loading tasks and patterns of muscle activation are thought to contribute to these injuries. The influence trunk and pelvis posture has on hip and thigh muscle activation during single leg stance is unknown and was investigated in a pain free population to determine if changes in body posture result in consistent patterns of changes in muscle activation. Methods: Hip and thigh muscle activation patterns were compared in 22 asymptomatic, male subjects (20-45 years old) in paired functionally relevant single leg standing test postures: Anterior vs. Posterior Trunk Sway; Anterior vs. Posterior Pelvic Rotation; Left vs. Right Trunk Shift; and Pelvic Drop vs. Raise. Surface EMG was collected from eight hip and thigh muscles calculating Root Mean Square. EMG was normalized to an "upright standing" reference posture. Repeated measures ANOVA was performed along with associated F tests to determine if there were significant differences in muscle activation between paired test postures. Results: In right leg stance, Anterior Trunk Sway (compared to Posterior Sway) increased activity in posterior sagittal plane muscles, with a concurrent deactivation of anterior sagittal plane muscles (p: 0.016-<0.001). Lateral hip abductor muscles increased activation during Left Trunk Shift (compared to Right) (p:= 0.001). Lateral Pelvic Drop (compared to Raise) decreased activity in hip abductors and increased hamstring, adductor longus and vastus lateralis activity (p: 0.037-<0.001). Conclusion: Changes in both trunk and pelvic posture during single leg stance generally resulted in large, predictable changes in hip and thigh muscle activation in asymptomatic young males. Changes in trunk position in the sagittal plane and pelvis position in the frontal plane had the greatest effect on muscle activation. Investigation of these activation patterns in clinical populations such as hip and thigh muscle injuries may provide important insights into injury mechanisms and inform rehabilitation strategies.